Monetary Policy and Exchange Rate Dynamics in a Behavioral Open Economy Model - Kolasa, Marcin (IMF Working Papers; Working Paper ;, 2022)
We develop an extension of the open economy New Keynesian model in which agents are boundedly rational a la Gabaix (2020). Our setup nests rational expectations (RE) as a special case and it can successfully mitigate many "puzzling" aspects of the relationship between exchange rates and interest rates. Since the model implies an uncovered interest rate parity (UIP) condition featuring behavioral expectations, our results are also consistent with recent empirical evidence showing that several UIP puzzles vanish when actual exchange rate expectations are used (instead of realizations implicitly coupled with the RE assumption). We find that cognitive discounting dampens the effects of current monetary shocks and lowers the efficacy of forward guidance (FG), but its relative importance in mitigating the so-called FG puzzle is decreasing in openness. Finally, we show that accounting for myopia exacerbates the small open economy unit-root problem, makes positive monetary spillovers more likely, and increases the persistence of net foreign assets and the real exchange rate.